Electrical excitability of neuronal networks based on the voltage threshold of electrical stimulation - Chen Meng; Yang Lu; Yan Huang; Xiaoying Lü (Scientific Reports)
Abstract Microelectrode arrays (MEAs) have been widely used in studies on the electrophysiological features of neuronal networks. In classic MEA experiments, spike or burst rates and spike waveforms are the primary characteristics used to evaluate the neuronal network excitability. Here, we introduced a new method to assess the excitability using the voltage threshold of electrical stimulation. We tested the stability of the voltage threshold during the experiment and demonstrated the reliability of our method by examining the effect of Ni2+ on neocortical neuronal networks of acute brain slices from rats. Moreover, we compared our new method with the spontaneous activity analysis, which is one of the most commonly used methods in protocols for large-scale drug screening with MEA; our new method performed better in the experiments investigating the neocortical neuronal network excitability after the application of Ni2+. Based on the results from our study, our new method has great potential for use in large-scale screening of drugs.